Nanoscale-trap-modulated electrical degradation in polymer dielectric composites using antioxidants as voltage stabilizers. (1st December 2019) - Su, Jingang; Du, Boxue; Han, Tao; Li, Jin; Li, Zhonglei; Xiao, Meng
Abstract: Electrical degradation is critical in polymer dielectric composites for increasing the upper voltage limit in today's harsh-environment electrical and electronic applications. Here, an attractive potential method for extending the electrical degradation durability by using antioxidants as voltage stabilizers is reported, which introduces efficient charge traps (or localization states) between the conduction and valence bands of polymer dielectric composites. The origin and mechanism of charge traps are identified in terms of the antioxidants' electronic structures via density functional theory calculations. When the trap sites are on the nanoscale (>1 nm) and have large deep trap energy levels, they can play an essential role in trapping charges in the free volume of the amorphous regions. According to the results of an electrical tree experiment, electrical degradation is substantially restrained by incorporating antioxidants into polymer dielectric composites. By investigating the charge migration in electron and hole trap sites, the polarity differences in electrical degradation are fully distinguished. The main characteristics of electrical degradation inhibition are identified, thereby offering a new approach for realizing high-performance polymer dielectric composites by improving electrical degradation resistance.